Use of condensed fermented corn extractives (liquid steep liquor) as a potential alternative for organic acids and probiotics in broiler ration - Marziyeh Hamidifard; Saeed Khalaji; Mahdi Hedayati; Hossein Rajaei sharifabadi (Italian Journal of Animal Science)
Condensed fermented corn extractives (liquid steep liquor) was assessed as an alternative to organic acids in broiler chicken. Day-old Ross 308 chicken (n = 180) were allocated into six treatments (basal diet with no supplement, basal diet supplemented with 1 and 2 cc/kg liquid corn steep liquor (CSL) or 1 and 2 cc/kg formic acid along with basal diet supplemented with probiotic (1 × 108 CFU/g, Lactobacillus acidophilus, Lactobacillus casei) in a completely randomised design with five replicate pens per treatment and six chicks in each pen. Broilers were assessed for performance measures and intestinal and serum characteristics. The results indicated that inclusion of CSL increased (p < .05) feed intake (FI) on days 1–21. Relative weight and length of different organs showed great differences among the treatments (p < .01). The pH content of different parts of the gastrointestinal tract reduced by inclusion of 1 cc/kg of CSL and formic acid (p < .05). Formic acid inclusion reduced villi length in comparison to the control group (p < .05). The lowest villi length to crypt depth ratio was determined in chicks fed diets supplemented with 1 cc/kg of CSL. Ileal and caecal microbial population did not alter by CSL or formic acid supplementation. CSL supplementation reduced the concentration of blood triglyceride, total and LDL cholesterol compared to the control group (p < .05). Results obtained from current trial revealed that CSL is an organic substance that have an acidic pH and its inclusion (1 cc/kg of diet) improved body weight on starter period and reduced digesta pH in gastrointestinal tract comparable to liquid formic acid, however, supplementation of CSL on higher dose (2 cc/kg od diet) did not change digesta pH considerably.HIGHLIGHTS Condensed fermented corn extractives (liquid Steep Liquor) was produced from Wet-milling of corn. Inclusion of 1 cc/kg of condensed fermented corn extractives improved growth performance of broiler chicken on starter period. Inclusion of 1 cc/kg of condensed fermented corn extractives reduced digesta pH.